Explaining the surprisingly weak relationship between organizational constraints and job performance. Issue 3 (26th May 2016) - Pindek, Shani; Spector, Paul E.
ABSTRACT: Organizational constraints are contextual factors that interfere with task performance. Study 1 was a meta-analysis of constraints-performance studies that found a smaller than expected relationship. Two additional studies were designed to understand why constraints fail to relate as expected to performance. Study 2 found support for the rater-bias hypothesis that raters take constraints into consideration when rating performance. Study 3 showed that constraints were both a challenge and a hindrance, and the two components tend to cancel one another. Two important conclusions that arise are that the constraints–performance relationship observed in field studies using raters is an underestimate of the true relationship, and constraints are not simply a hindrance, but can have a challenging effect that enhances motivation, as well.